Study of martensite transformation and microstructural evolution of Cu-Al-Ni-Fe shape memory alloys - Yildiz, Koksal; Kok, Mediha (Springer, 2014)
In this study, variations in the transformation temperature, crystal structure, and microstructure of the arc melted alloy having nominal composition of Cu-13%Al-4%Ni-4%Fe (in mass%) were investigated for two different treatment conditions, homogenized and heat treated at 950 A degrees C for 1 h. For both conditions, transformation temperature of the alloy was examined by DSC and it was determined as similar to 200 A degrees C, similar to the value for Cu-Al-Ni alloys given in the literature. The crystal structure of the martensite Cu-13%Al-4%Ni-4%Fe (in mass%) alloy was identified as 18R using XRD. By heat treatment performed at 950 A degrees C, diffraction peaks become more distinct. The microstructure of the alloy was studied with the help of optical microscope as a result of which parallel martensite plates and precipitates were detected. Microhardness value of the alloy was found as 361 and 375 Hv for homogenized and heat-treated conditions, respectively.
Keywords: Cu-Al-Ni-Fe alloy; Martensite transformation; Heat treatment; Differential scanning calorimetry; Microhardness